2017
DOI: 10.1039/c7cc00317j
|View full text |Cite
|
Sign up to set email alerts
|

Isotopically enriched polymorphs of dysprosium single molecule magnets

Abstract: A triclinic polymorph Dy(t) and a monoclinic polymorph Dy(m) of [Dy(tta)(L)] with L = 4-[6-(1,3-benzothiazol-2-yl)pyridin-3-yl]-4',5'-bis(methylthio)tetrathiafulvene behave as Single-Molecule Magnets with hysteresis loops opened at zero field. Magnetic properties were enhanced through magnetic dilution and Dy isotopic enrichment which definitively support the importance of isotopes for the control of quantum magnets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 31 publications
4
41
0
Order By: Relevance
“…It was previously demonstrated that the rotation of the ligand L 1 depends on the size of the lanthanide ion. [43] The isomer observed in 5 and 6 is in agreement with the monoclinic phase observed for the Y III and Dy III analogues. The C=C central bond length of the TTF core of 1.332(14) Å [1.312 (19) Å] again attests to the neutrality of L 1 .…”
Section: (L 1 )] [Ln = Yb (5) and Er (6)]supporting
confidence: 73%
See 3 more Smart Citations
“…It was previously demonstrated that the rotation of the ligand L 1 depends on the size of the lanthanide ion. [43] The isomer observed in 5 and 6 is in agreement with the monoclinic phase observed for the Y III and Dy III analogues. The C=C central bond length of the TTF core of 1.332(14) Å [1.312 (19) Å] again attests to the neutrality of L 1 .…”
Section: (L 1 )] [Ln = Yb (5) and Er (6)]supporting
confidence: 73%
“…The precursors Ln(hfac) 3 ·2H 2 O, Ln(tta) 3 ·2H 2 O, [57,58] [43] 4,5-(ethylenedithio)tetrathiafulvalene [59] and 2-(5-bromopyridin-2-yl)-1,3-benzothiazole, [60,61] were synthesized by previously reported methods. All other reagents were purchased from Aldrich Co., Ltd. and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[41] The utilization of 164 Dy(III) (I = 0) led to the observation of enlarged hysteresis loops at zero field, in comparison to SMMs obtained from the naturally occurring isotopic mixture. Concerning the first point, although 159 Tb-based SMMs seem promising candidates as nuclear spin qubits, the non-Kramers character of the Tb(III) ion has led to a very limited number of examples of Tb(III)-based SMMs with satisfyingly strong magnetic anisotropy.…”
Section: Linear Scaling: Nuclear Spin Multiplicity In Mononuclear Isomentioning
confidence: 99%